Universal Design for Learning (UDL) in the Islamic Religious Education Assessment Model: Systematic Literature Review (Jurnal Sustainable, 2024)
Current curriculum developments place greater emphasis on developing learning models and methods that can accommodate students' differences in learning styles and abilities. In the independent curriculum, this concept is better known as differentiated learning. One concept that can facilitate differentiated learning in the context of assessment is Universal Design for Learning (UDL). Using a Systematic Literature Review (SLR) approach, this research aims to analyze the effectiveness of implementing assessment models in PAI learning in the UDL context. The findings of this research indicate that the assessment model that is widely applied to PAI learning is the authentic assessment model. Based on educational level, this authentic assessment model is more widely applied at the junior secondary education level (SMP/MTs). Based on the results of the analysis of articles that met the inclusion criteria, no evidence was found regarding the effectiveness of its implementation which had an impact on PAI learning processes and outcomes. The findings of this research can be used as an empirical basis for conducting research that focuses on the influence of implementing assessment models on PAI learning processes and outcomes.